Input from stakeholders: Hiring and retaining people in Recovery in the behavioral health workforce - Bellamy, Chyrell; McDonald, Heather E.; Hawkins, Dietra; Guy, Kimberly; Herring, Yolanda; Davidson, Larry (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2017)
The hiring of people in recovery (PIR) from mental illnesses in the behavioral health workforce has bloomed in the past few years. PIR have been hired in a variety of positions including as peer supporters, case managers, clinicians, and CEOs. This paper highlights findings from focus groups that were conducted with behavioral health organizations to gather input on hiring and retaining PIRs in the behavioral health workforce. Suggestions were mostly targeted to the areas of 1) Hiring Peers— the value and benefits and challenges, and suggestions for organizational readiness and, 2) Retaining PIRs—transitioning PIRs to the behavioral health workforce and supervision, flexibility and accommodations. Input from these discussions has informed the creation of development and implementation guides for organizations wanting to hire PIRs as peer supporters. In addition to the development of training guidelines for PIRs in roles as peer supporters. This paper signifies the importance of gathering input prior to developing implementation initiatives on the employment of PIRs as peer supporters, in the behavioral health workforce.